(untitled) (Kronika Bydgoska, 2020)
The history of education in Bydgoszcz and its area has not been sufficiently explored. It also applies to Protestant education. There are not too many publications dedicated to this topic. This article is supposed to fill one of the gaps regarding this issue. For this purpose, the author analyzed visitations of the Superintendent carried out in 1796-1800, contained in the unit composing the group The Files of the Superintendency in Toruń. He conducted comparative analysis between individual Protestant schools located in Bydgoszcz and Fordon, and in ten villages around these cities. Studies have been dedicated to specific location and performance of school supervision. An attention was also focused on teachers. The author presented teaching personnel, providing their names, surnames and age, and - according to available information - their qualifications and vocational experience. Their means of subsidence, including salaries and benefits in kind, were described as well. As regards students, the article focused on the number of students attending individual classes and schools as well as possessing or lacking elementary skills in terms of literacy and numeracy.